Selected Physical Properties of Andisols under Different Land Use Condition in Gunung Kerinci Subdistrict, Jambi - Endriani, . (JOURNAL OF TROPICAL SOILS, 2010)
Selected Physical Properties of Andisols under Different Land Use Condition in Gunung Kerinci Subdistrict, Jambi (Endriani):  Objective of the research was to study the effect of different land use at some land slope condition on some physical properties of Andisols in Gunung Kerinci Subdistrict, Jambi.. The research was conduct using field survey and purposive random sampling methods to collect soil.  The land use which was using in this study were: forest,  cultivation,  cinnamon, and coffee plantation, while land slope level weres: 3-8%,  8-15%, 15-25 %, and > 25%.  The results showed that  among land use types, the rank of soil  physical properties, such as: soil organic matter, bulk density, porosity, percentage of  agregation, stability of agregate, pore distribution and permeability were in order of : forest > cultivation > cinnamon > coffee.  Land conversion from forest to agricultural land caused decreasing in  the soil physical properties.  The higher level of land slope caused the decreasing of soil physical properties  at all type of  land use.